Effectiveness of Different Nitrogen Sources on Leucaena leucocephala - Singh, S. B.; Kumar, Pramod; Prasad, K. G. (Indian Forester, 1991)
A quadruplicate experiment In 11 Ã— 3 factorial (11 treatments Ã— 3 sampling time) with a control set was conducted to see the effectiveness of different N sources i.e. organic, ammonlcal, nitrate and ammonlcal + nitrate on Laucaena. leucocephalai applied through urea (U) and mud coated urea (MU), ammonium sulphate (AS), sodium nitrate (SN) and ammonium nitrate (AN) respectively @ 45 and 90 ppm. The height, biomass production, nitrogen use efficiency (NUE) and nitrogen reductage (NR) activity In plant were noted after 6, 9 and 12 months of treatments.